2014
DOI: 10.1177/0020764014535752
|View full text |Cite
|
Sign up to set email alerts
|

Mental health interventions for traumatized asylum seekers and refugees: What do we know about their efficacy?

Abstract: This review has again highlighted the shortage of guiding frameworks available to investigators and clinicians who are interested in tailoring interventions to work with refugees and asylum seekers. Theoretical, ethical and methodological considerations for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(122 citation statements)
references
References 71 publications
(98 reference statements)
1
110
0
3
Order By: Relevance
“…European mental health care services generally offer psychotherapist or psychiatrist delivered, specialized mental health services that may involve a wide range of treatments, such as Cognitive Behavioural Therapy (CBT), Narrative Exposure Therapy (NET) (Stenmark, Catani, Neuner, Elbert, & Holen, 2013), Eye Movement Desensitization and Reprocessing (EMDR) (Ter Heide, Mooren, Kleijn, de Jongh, & Kleber, 2011), and individual-based multimodal interventions for PTSD (see Nickerson, Bryant, Silove, & Steel, 2011; Nose et al, 2017; Slobodin & de Jong, 2015; van Wyk & Schweitzer, 2014 for reviews) in refugees and asylum seekers. With respect to evidence for such interventions, a recent meta-analysis that examined psychological interventions for symptoms of PTSD in refugees and asylum seekers resettled in high-income countries identified 14 randomized controlled trials (RCTs) (Nose et al, 2017).…”
Section: Evidence-based Interventions For Refugeesmentioning
confidence: 99%
“…European mental health care services generally offer psychotherapist or psychiatrist delivered, specialized mental health services that may involve a wide range of treatments, such as Cognitive Behavioural Therapy (CBT), Narrative Exposure Therapy (NET) (Stenmark, Catani, Neuner, Elbert, & Holen, 2013), Eye Movement Desensitization and Reprocessing (EMDR) (Ter Heide, Mooren, Kleijn, de Jongh, & Kleber, 2011), and individual-based multimodal interventions for PTSD (see Nickerson, Bryant, Silove, & Steel, 2011; Nose et al, 2017; Slobodin & de Jong, 2015; van Wyk & Schweitzer, 2014 for reviews) in refugees and asylum seekers. With respect to evidence for such interventions, a recent meta-analysis that examined psychological interventions for symptoms of PTSD in refugees and asylum seekers resettled in high-income countries identified 14 randomized controlled trials (RCTs) (Nose et al, 2017).…”
Section: Evidence-based Interventions For Refugeesmentioning
confidence: 99%
“…Three reviews have examined the efficacy of rehabilitation programs and treatment outcomes (McFarlane & Kaplan, 2012;Palic & Elklit, 2011;Slobodin & de Jong, 2015). The reviews found modest reductions in psychopathological symptoms among refugees.…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 99%
“…In the post-migration phase, refugees often meet substantial challenges (ACPMH, 2007;Murray, Davidson, & Schweitzer, 2010). Adverse experiences such as discrimination and acculturation difficulties are common, requiring higher levels of functioning than many refugees have (ACPMH, 2007;Davidson, Murray & Schweitzer, 2008;Slobodin & de Jong, 2015;Sachs, 2011). By virtue of their traumatic and adverse experiences, refugees have an elevated risk of developing physical, social, and psychological…”
Section: Introductionmentioning
confidence: 99%
“…A eficácia da Terapia de Exposição Prolongada que explora a exposição às memórias traumáticas, às imagens traumáticas e o processamento dessas memórias acompanhada de um processo psicoeducacional é apoiada por um grande número de estudos efetuados sobre variadas populações e em diversos contextos culturais (McLean & Foa, 2011). Mas o assunto é controverso havendo autores que argumentam a necessidade do tratamento inicial se concentrar em problemas da vida diária e na restauração da capacidade de enfrentamento das situações (Slobodin & de Jong, 2014). Slobodin e de Jong (2014) defendem que a Terapia Cognitivo Comportamental e a Terapia de Exposição Narrativa são as estratégias mais eficazes para estas populações concluindo não haver dados suficientes para confirmar ou refutar abordagens alternativas, como a intervenção em grupo, intervenção familiar ou abordagem multidisciplinar no trabalho com refugiados traumatizados e requerentes de asilo.…”
Section: Perturbação Pós-stress Traumático (Ptsd)unclassified
“…As intervenções de natureza psicoterapêutica nestas populações são sempre difíceis uma vez que, a tradução da linguagem tantas vezes necessária, faz perder as nuances da comunicação e o tempo que demora a ser feita encurta de sobremaneira as sessões (Buhmann, 2014). O tratamento farmacológico de eleição para a PTSD nestas populações são os antidepressivos do subgrupo dos Inibidores Seletivos da Recaptação da Serotonina especialmente a Sertalina (Slobodin & de Jong, 2014).…”
Section: Perturbação Pós-stress Traumático (Ptsd)unclassified